Plantando agroflorestas, colhendo transformações: transição agroecológica e alimentação em uma comunidade quilombola no Vale do Ribeira - Silva, Ana Rita (2021)
Considering that the conformation of the current food system imposes several obstacles to the social reproduction of peasant agriculture, exploring alternatives that reduce social inequality in the countryside, environmental damage and that value Sovereignty and Food and Nutritional Security is of fundamental importance. In view of this, this research had as its main objective the study of agroforestry systems as a strategic tool for the agroecological transition from fragile traditional systems, highlighting the main changes, especially with regard to the feeding of families. To this end, fieldwork was carried out in the Remanescente Quilombola Community (CRQ) Areia Branca, located in Vale do Ribeira, southeastern Brazil. This is a typically rural region and has one of the lowest Human Development Indexes (HDI) in the country, however, in recent years, it has stood out with relevant experiences in the adoption of agroecologically based systems. The research had a qualitative approach, using the following methodological instruments: bibliographic survey, application of semi-structured interviews and direct observation. The results demonstrate that the SAFs made it possible to strengthen the relative autonomy of farming families in agricultural production and commercialization, as well as in food. However, the interconnection of various components that acted as facilitators in this process should be considered, in particular the action of the Cooperafloresta association, which provided the construction of knowledge, stimulated the strengthening of collective ties between families and provided means that enabled the flow of production. In general, this work provides data that help to understand how agroforestry systems, developed within an agroecological approach, enable social, economic and food transformations, based on Food and Nutritional Sovereignty and Security, contributing to the (re)production of agriculture peasant.